Minat baca Cara efektif meningkatkan minat baca pada kelompk B3 di TK Muslimat NU 1 Sukolilo dengan Menggunakan Media Talking Stick - Diyaalya, Khorida Lutfi (Maliki Interdisciplinary Journal, 2024)
The purpose of this study is that as learning actions in the classroom need to be considered by teachers on how to effectively increase reading interest through the talking stick method. The use of Talking Stick media in learning is expected to create a more inclusive and participatory learning atmosphere. With this method, every child gets an equal opportunity to talk and interact, so that their interest in reading can be stimulated through activities that involve children.In the process of observation in order to examine the extent to which this talking stick media can be used and become a material or teaching media that can be applied during the learning process. Through this approach, it is hoped that children will not only be interested in reading, but also develop better literacy skills overall.